HealthMpowerment.org: Building Community Through a Mobile-Optimized, Online Health Promotion Intervention. (August 2015) - Hightow-Weidman, Lisa B.; Muessig, Kathryn E.; Pike, Emily C.; LeGrand, Sara; Baltierra, Nina; Rucker, Alvin Justin; Wilson, Patrick
Background . Both young Black men who have sex with men as well as young Black transgender women (YBMSM/TW) continue to experience a significant increase in HIV incidence.HealthMpowerment.org (HMP) is a mobile phone-optimized, online intervention for both YBMSM/TW to build community and facilitate supportive relationships. Methods . To assess the feasibility, acceptability, and preliminary outcomes, a 1-month pilot trial of HMP among 15 YBMSM/TW was conducted. Results . Retention was 100%. Mean age was 26 years, 60% were HIV-infected, 87% earned <$21, 000, and 67% were uninsured. Despite the small sample size and limited intervention length, statistically significant improvements were seen in social support ( p = .012), social isolation ( p = .050), and depressive symptoms ( p = .045). Conclusion . The HMP pilot trial demonstrated feasibility and acceptability. Given the burden of the epidemic among YBMSM/TW, there is an imperative to develop, test, and scale up culturally appropriate interventions to both prevent HIV acquisition and limit onward transmission.